1999
DOI: 10.1055/s-1999-152
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Endoscopic and Percutaneous Transhepatic Treatment of Benign Biliary Strictures

Abstract: Endoscopic and percutaneous treatment of benign biliary strictures is not only a short-term treatment, but also an adequate long-term therapeutic alternative to surgery, with tolerable complication rates. The period of stenting appears to influence the outcome, and the diameter of the stents used also probably plays a role. Prospective studies are required for further evaluation of these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
2
8

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 30 publications
1
42
2
8
Order By: Relevance
“…Surgical reintervention is associated with morbidity and mortality rates as high as 28 and 2.6 % respectively [26]. Percutaneous treatments represent an effective alternative to surgery in the treatment of such complication [27][28][29]. To achieve resolution of the stenosis, subsequent larger biliary drainage catheter may be inserted and left in place and balloon dilation can be performed.…”
Section: Percutaneous Transhepatic Biliary Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical reintervention is associated with morbidity and mortality rates as high as 28 and 2.6 % respectively [26]. Percutaneous treatments represent an effective alternative to surgery in the treatment of such complication [27][28][29]. To achieve resolution of the stenosis, subsequent larger biliary drainage catheter may be inserted and left in place and balloon dilation can be performed.…”
Section: Percutaneous Transhepatic Biliary Proceduresmentioning
confidence: 99%
“…To achieve resolution of the stenosis, subsequent larger biliary drainage catheter may be inserted and left in place and balloon dilation can be performed. However, recurrence of stenosis may occur in up to 29-58 % of cases [27][28][29], and multiple treatment sessions may be required. Stents are rarely used in the treatment of benign strictures, as they have to be removed after a period because the tube itself may stimulate inflammatory reaction, fibrosis and stone formation.…”
Section: Percutaneous Transhepatic Biliary Proceduresmentioning
confidence: 99%
“…In der Regel sind bis dahin mehrere endoskopische Wechsel der Prothese im Abstand von 3 Monaten notwendig. Vorteile dieses Vorgehens sind die geringe Invasivität und eine gute langfristige Wirksamkeit [9,10]. Die Erfolgsquote ist dabei abhängig von der Genese und Lokalisation der Stenose.…”
Section: Behandlungsmöglichkeiten Bei Benignen Gallengangstenosenunclassified
“…Die Punktionsnadel (weißer Pfeil) verlässt das im Bulbus duodeni positionierte Gerät und erreicht den erweiterten DHC proximal der bekannten Stenose (schwarzer Pfeil) zum endoskopischen Verfahren liefert die PTCD bei der Behandlung benigner Stenosen mindestens gleichwertige langfristige Erfolgsraten. Das gute Abschneiden wird u. a. damit erklärt, dass mittels PTCD das Einbringen größerer Katheterkaliber möglich ist [10]. In unserem Fall kamen zuletzt Yamakawa-Prothesen mit einem Durchmesser von 20 French zum Einsatz, wohingegen in der enteroskopischen retrograden Cholangiopankreatikographie meist deutlich kleinere Durchmesser verwendet werden.…”
Section: Behandlungsmöglichkeiten Bei Benignen Gallengangstenosenunclassified
“…Therefore, a high index of suspicion is required to ensure a proper diagnosis. To prevent irreversible fibrosis, an early diagnosis of biliary stricture is essential in order to allow timely treatment with percutaneous or endoscopic intervention [3,5,9] . Several workers have suggested that endoscopic stent placement is an effective treatment for suprapancreatic biliary strictures caused by blunt abdominal trauma [5,10,11] .…”
mentioning
confidence: 99%